Using design-thinking to investigate and improve patient experience - Jennifer Smiechowski; Megan Mercia; Kyle Kemp; Elizabeth Oddone Paolucci; Maria Santana; Rahim Kachra (The Beryl Institute, 2021)
Understanding and enhancing the patient experience can lead to improved healthcare outcomes. The purpose of this study was to capture a comprehensive and nuanced understanding of the patient experience on an inpatient medical teaching unit in order to identify key deficiencies and unmet needs. We then aim to implement a design-thinking methodology to find innovative ways to solve these deficiencies. Here we present the first two phases of this four-phased study. We retrospectively and prospectively collected quantitative data about patient experience with the Canadian Patient Experiences Survey-Inpatient Care. We then used this data to guide patient interviews. We identified several key deficiencies including call bell response times, noise levels at night, pain control, education about medication side effects, communication between healthcare team members, and how well healthcare team members remain up to date about patient care. In the final two phases of our study, we will select one or more of these deficiencies and collaborate with patients and other stakeholders to rapidly create, employ, and assess the impact of prototypes through an iterative action cycle until effective and sustainable solutions are found. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens